Validation of the α-μ Model of the Power Spectral Density of GPS Ionospheric Amplitude Scintillation - Kelias Oliveira; Alison de Oliveira Moraes; Emanoel Costa; Marcio Tadeu de Assis Honorato Muella; Eurico Rodrigues de Paula; Waldecir Perrella (International Journal of Antennas and Propagation)
The α-μ model has become widely used in statistical analyses of radio channels, due to the flexibility provided by its two degrees of freedom. Among several applications, it has been used in the characterization of low-latitude amplitude scintillation, which frequently occurs during the nighttime of particular seasons of high solar flux years, affecting radio signals that propagate through the ionosphere. Depending on temporal and spatial distributions, ionospheric scintillation may cause availability and precision problems to users of global navigation satellite systems. The present work initially stresses the importance of the flexibility provided by α-μ model in comparison with the limitations of a single-parameter distribution for the representation of first-order statistics of amplitude scintillation. Next, it focuses on the statistical evaluation of the power spectral density of ionospheric amplitude scintillation. The formulation based on the α-μ model is developed and validated using experimental data obtained in São José dos Campos (23.1°S; 45.8°W; dip latitude 17.3°S), Brazil, located near the southern crest of the ionospheric equatorial ionization anomaly. These data were collected between December 2001 and January 2002, a period of high solar flux conditions. The results show that the proposed model fits power spectral densities estimated from field data quite well.